A meta-synthesis of competency standards suggest allied health are not preparing for a digital health future. (December 2020) - Butler-Henderson, K.; Dalton, L.; Probst, Y.; Maunder, K.; Merolli, M.
Abstract: Objective: This study reviewed the competency and threshold standards for allied health professionals to identify the inclusion of digital health competencies. Materials and methods: A nine-stage, sequential meta-synthesis of professional standards was undertaken. Statements relevant to digital health were extracted, categorised by discipline, and coded to the level in the standards, skills or knowledge and level of learning. Results: Eighteen standards were analysed. Of these, fourteen standards contained a total of thirty-five statements related to digital health in the themes of data governance and technologies, but not data translation. Only four disciplines included more than two statements related to digital health. Discussion: The study highlighted four key gaps in the Standards. Statements in competency and threshold standards for allied health professionals lack reference to digital health, with predominantly information management statements. The statements are ambiguously worded, and could be interpreted to only refer to paper records management, and when there is a reference to digital health, it is more likely to be a skill as opposed to knowledge, typically at the indicator or cue level, and largely a lower level of learning (Bloom's). The lack of digital health in standards may result in limited instruction in already full tertiary education curriculum. Conclusion: Digital health represents a major gap in competency statements for all allied health disciplines, signifying the need for a national approach to developing quality and specific digital health competencies, to support allied health graduates being prepared to work in the digital health age.